(untitled) (Journal of Engineering and Health Sciences, 2022)
The AHP methods has been proposed because the decision theory has become a useful tool for maintenance decision making the analysis thereof, focuses not only on making a decision, its goal is also to provide insight in the decision process. AHP contributes to analyses the decision-making context, organizing the process, increasing coherence on the goals and the final decision, and cooperation between the decision makers, leading to a better mutual understanding. It decomposes decision-making into the following using the priorities obtained from the elements at one level to weigh the priorities of the elements in the level immediately below them. The AHP is selected for this research because it is a well-established multiple criteria decision-making approach, both in academia and industry. Its specific benefits are designed to integrate objective, subjective, qualitative and quantitative information. Moreover, AHP creates a thorough understanding of the problem by structuring the problem hierarchically, compares the criteria and alternatives pairwise, providing simplicity and ease of use and produces plausible and defensible results.